Explorations on the Abbasids political culture in pursuit of sustainable system of governance in the Muslim world - Shuriye, Abdi Omar (MCSER Publishing, Rome-Italy, 2016)
Today democracy and good governance are absent from the Muslim world. Some attribute this to the religion of Islam itself while others, the mainstream of the world community, have attributed it to the Muslims themselves. The two however are intertwined and the later is on a course to a distractive paint of the former. History manifests itself in diverse ways and contemporary political outlook of the Muslim world is not a new phenomenon. The main objective of this study is to provide insights into the history of Muslim political thought; the Abbasid dynasty is the case under examination. One argues that the main contribution of the Abbasids is the development of a strong political system which has eventually led to a political stability and a steady economic growth. The political characteristics and the economic development during the Abbasid period, which was later recognized as the Golden Era in the Muslim political history, are the main focus of this work. This is crucial in order to understand the political backbone of the dynasty. Foreign relations which also contribute to the rise and the fall of Abbasids are also evaluated. Reassessment of the religious and political or territorial conflicts against other nations will be principal discourse in this work.